Vaccines: A Biography - Artenstein, Andrew W. (Springer New York, 2010)
Recounting the social, cultural, and scientific history of vaccines, Vaccines: A Biography traces the lineagethe biographyof individual vaccines, originating with deeply rooted medical problems, following ideas as they are conceived and developed, leading eventually to practical, preventive solutions to major public health problems in society. Yet these are not biographies in the traditional sense; they do not trace an individuals growth and development. These are epic stories of discovery, of risk-takers. They have all the trappings of fiction: strong protagonists who succeed against sometimes great odds, interpersonal conflicts, deceit, political intrigue, ethical dilemmas, and dramatic, if not staged events. They are set in the major centers of Europe and the United States, on farms and in slums, and in exotic venues from Calcutta to French Indochina to Cairo to Panama. They occur in the halls of academia, research laboratories, the chambers of government, and on the battlefields of war. At its core, Vaccine: A Biography is the history of individuals advancing medical science, in the words of the famous physical scientist Isaac Newton, "by standing on the shoulders of giants".